Pengaruh Kreativitas Belajar dan Kecerdasan Emosional Terhadap Prestasi Belajar Matematika Ekonomi - Nurhayati Nurhayati (Pusat Riset dan Inovasi Nasional, 2021)
The purpose of this study was to analyze the effect of learning creativity and emotional intelligence on economic mathematics learning achievement of students at Stie Ganesah Jakarta. This research is a quantitative survey research with a correlation approach. The respondents in this study were first semester students of the STIE Ganesha Economics study program. The data were obtained by giving the students' learning creativity and emotional intelligence questionnaires. This is evidenced by the value of Sig = 0.011 <0.05 and t count = 2.696. The magnitude of the correlation number is 0.389 with a determination of 0.151. This means that the magnitude of the relationship between X1 and X2 variables to Y is 0.389 with a medium category. The magnitude of the effect of X1, X2 on Y is 15.1% where the variables of learning creativity and emotional intelligence together affect the variable of student achievement in mathematics economics by 15.1% while the rest is influenced by other variables.